Effects of a Teacher-Training Violence Prevention Program in Jamaican Preschools on Child Behavior, Academic Achievement, and School Attendance in Grade One of Primary School: Follow up of a Cluster Randomized Trial - Baker-Henningham, Helen; Scott, Yakeisha; Francis, Taja; Walker, Susan P. (Frontiers in Psychology, 2021)
Objective We evaluated the effect of a universal, teacher-training, violence-prevention program implemented in preschool, on high-risk children’s behavior, achievement, and attendance in grade one of primary school. Methods A cluster-randomized trial was conducted in twenty-four preschools in Kingston, Jamaica. Three children from each class with the highest level of teacher-reported conduct problems were recruited for evaluation of outcomes (n=225 children). For this study, to increase power, we recruited an additional two children from each class with the next highest teacher-reported scores for conduct problems in preschool. In the final term of grade one of primary school, we assessed children’s: 1) conduct problems and social skills at home and school, 2) academic achievement, language, and self-regulation skills, and 3) school attendance. Results 214/225 (95.1%) of the children evaluated in preschool were assessed in grade one of primary school; an additional 150 children were recruited to give 364 children (181 intervention, 183 control). Significant benefits of intervention were found for child academic achievement (ES= 0.23, p=0.02), oral language (ES=0.28, p=0.006), self-regulation (ES=0.25, p=0.007), and school attendance (ES=0.30, p=0.003). No significant benefits were found for observed conduct problems (ES=-0.13, p=0.16), and parent-reported conduct problems (ES=0.10, p=0.31) and social skills (ES=-0.07, p=0.52). Benefits to teacher-reported conduct problems and social skills were significant at p<0.1 (ES=-0.16, p=0.09 and ES=0.19, p=0.06 respectively). Conclusion A scalable intervention involving training preschool teachers in classroom behavior management and how to promote child social-emotional competence led to positive outcomes in primary school across multiple child developmental domains for high-risk children.